Upaya Sekolah Dalam Menumbuhkembangkan Karakter Disiplin dan Religius Siswa Di SMAN 1 Brang Rea Sumbawa Barat - Kemas Arjuna Inayatullah; Mustari, Mohammad; Muh. Ismail (Journal of Social and Education, 2024)
Character education is a learning process to form good and quality character. One of the character values ​​that needs to be developed is discipline and religious character. Disciplinary and religious character values ​​are very important for a human being, especially students, so that other good character values ​​emerge. The purpose of this research is to determine the efforts made by schools to develop students' disciplinary and religious character, supporting and inhibiting factors for schools in developing students' disciplinary character. This research uses a qualitative approach with a descriptive type. Data sources consist of primary and secondary data sources. The informants in this research were the school principal, teachers and head of student affairs. Data collection techniques use observation, interview and documentation techniques. The data analysis techniques used are data reduction, data presentation and drawing conclusions. Testing the validity of the data is triangulation of technique, source and time. The results of the research show that the school's efforts to develop students' disciplined character are through programs in the form of implementing the 3S culture which is carried out in front of the gate in the morning, Koran literacy activities which are carried out every morning, and congregational noon prayers which are held from Monday to Thursday. The supporting factors include facilities and infrastructure, human resources (HR) and students' awareness of the importance of discipline, then the inhibiting factors are the family environment and social environment. The impact of implementing school programs in developing disciplinary character is that there are changes that occur in students' daily lives, especially in disciplinary character.